Business Model Canvas and Digital Marketing Approach to Increase Market Share: A Case Study of View Point Resto Lahangan, Karangasem - Sukerna, I Made; Elik Astari , Anak Agung; Andini Desiyanti Laksmi, Ni Putu (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study aims to analyze the application of the Business Model Canvas (BMC) approach and digital marketing strategies in an effort to increase the market share of View Point Resto Lahangan, Karangasem. Amidst increasingly fierce competition in the culinary industry, the use of a structured business model and digital-based marketing strategies are key factors in attracting customers and expanding market reach. The research method used is a case study with a qualitative approach, through in-depth interviews, direct observation, and secondary data analysis. Based on the comprehensive research and discussion, it can be concluded that the internal strategy factor analysis (IFAS) showed a total score of 3.34, indicating that this restaurant has a strong internal strategy to address its weaknesses. Meanwhile, the external strategy factor analysis (EFAS) obtained a total score of 3.18, indicating the restaurant's ability to respond well to external factors and utilize existing opportunities to overcome threats. Furthermore, from the Business Model Canvas analysis review, this business demonstrates a strong foundation. This restaurant targets all age groups and offers attractive value propositions, such as friendly service, fresh products, prices commensurate with quality, and environmentally friendly packaging. Customer relationships are built through the website and educational content, while revenue streams are supported by varied product prices and various payment systems